PENGARUH PENGOBATAN HERBAL SPRAY BERBASIS BIOAKTIF DARI SPIRULINA (SPIRULINA SP.) TERHADAP PROFIL PROTEIN LUKA DAN HISTOLOGI PANKREAS TIKUS (RATTUS NORVEGICUS) TERPAPAR MULTIPLE LOW DOSE STREPTOZOTOCIN (MLD-STZ) - Mahdi, Chanif; Rahma, Kartika; Aulanni'am, Aulanni'am (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
This research aims to determine the effect of Spirulina sp. extracts in the form of spray on pancreatic tissue histology, and protein profiles of skin wound rats (Rattus norvegicus) induced by Multiple Low Dose streptozotocin (MLD-STZ). The injection of MLD-STZ at a dose of 20 mg/kg BW causes Diabetes Mellitus (DM) type 1. In this study, rats were divided into 3 groups: negative control (no STZ induction), positive control (MLD-STZ-induced), and therapy group (MLD-STZ-induced and therapy). Therapy was given in the form of spray-based herbal bioactive Spirulina sp. with a dose of ± 200 μL right on rat wound 3 times/day during 2 weeks after being DM as a result of MLD-STZ induced. The method used for the analysis of protein is SDS-PAGE and pancreatic tissue histology using hematoxylin-eosin staining methods (HE). The results of the study showed that post-therapy causes the difference of protein band profiles of the three treatment groups, emergence a new protein band with a molecular weight of 93 kDa in skin wounds of diabetic rats, and this protein bands disappear in skin wound rats after treated by herbal spray of Spirulina sp.. In addition, results of histological pancreatic tissue diabetic group has reduction of pancreatic β cells and islet of Langerhans in the cavity width. As well, there is improvement in the therapy group of pancreatic histology.Keywords: diabetes mellitus, pancreatic histology, skin protein bands